2010
DOI: 10.1111/j.1750-3841.2010.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Lexicon for Sensory Descriptive Profiling of Different Rice Types

Abstract: Rice flavor is a significant factor in determining quality and consumer acceptability as exemplified by scented rice, which is highly favored and commands a price premium. Sensory descriptive analysis has primarily been performed to assess rice flavor characteristics, but these studies feature only a limited lexicon for characterizing specific flavors or the range of flavor types is limited. This study was undertaken to establish a descriptive lexicon with reference standards for describing the flavor properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…However, Figure 8, showing the metabolomic signatures of the varieties in this paper, and other studies working with jasmine and basmati types [65], [66] have shown that other compounds and fragrance descriptors also contribute to the aroma of jasmine and basmati rices. Given the importance of these three classes of rice to Iran, Pakistan and to some states of India, and the countries in the GMS, it seems that improving yields in those regions requires a deeper understanding of the important compounds of fragrance for each type, and research to deliver robust phenotyping tools that are able to distinguish between the three types of aroma.…”
Section: Resultsmentioning
confidence: 54%
“…However, Figure 8, showing the metabolomic signatures of the varieties in this paper, and other studies working with jasmine and basmati types [65], [66] have shown that other compounds and fragrance descriptors also contribute to the aroma of jasmine and basmati rices. Given the importance of these three classes of rice to Iran, Pakistan and to some states of India, and the countries in the GMS, it seems that improving yields in those regions requires a deeper understanding of the important compounds of fragrance for each type, and research to deliver robust phenotyping tools that are able to distinguish between the three types of aroma.…”
Section: Resultsmentioning
confidence: 54%
“…Rice is considered as a good model for quinoa lexicon development because both products have common preparation methods. Lexicons for cooked rice have been developed for its aroma, taste/flavor, and texture properties (Lyon and others ; Meullenet and others ; Limpawattana and Shewfelt ). Many attributes from these previously developed rice lexicons can be applied to cooked quinoa.…”
Section: Resultsmentioning
confidence: 99%
“…The samples widely varied in their sensory attributes and included the varieties “Black,” “Bolivia Red,” and “Bolivia White.” The panelists developed terms to describe the appearance, aroma, flavor, taste, and texture of the samples. These attributes from the trained panelists were collected, along with terms from the literature describing rice (Meilgaard and others ; Limpawattana and Shewfelt ). The attribute list was presented and discussed, with panelist consensus being used to determine which sensory attributes appeared in the final lexicon.…”
Section: Methodsmentioning
confidence: 99%
“…The intensities of corn/popcorn/buttery flavors, dairy flavors, and sweet taste attributes commonly associated with white rice (Bett-Garber et al 2001;Limpawattana and Shewfelt 2010) were significantly different between bran colors based on analysis of variance results (Table II). Dairy flavor and sweet taste were significantly more intense in the brown bran rice than in the red and the black or purple rice, whereas corn/popcorn/buttery was more intense in brown than in red rice (Table III).…”
Section: Comparison Of Whole Grain Rice Flavor and Taste Attributesmentioning
confidence: 96%